2019
DOI: 10.1016/j.heliyon.2019.e01716
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Zn-Doped hydroxyapatite: scaffold application, antibacterial and bioactivity studies

Abstract: In this study, the antimicrobial and scaffold of zinc-substituted hydroxyapatite, (Zn-HAp) synthesized via chemical co-precipitation technique was investigated. The structure of the synthesized Zn-HAp was investigated with X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, Scanning electron microscope (SEM), Energy dispersive X-spectroscopy (EDAX), transmission electron microscope (TEM), Thermogravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS). Bioactivity study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(89 citation statements)
references
References 36 publications
5
84
0
Order By: Relevance
“…However, after a certain time interval (60 min) no further enhancement in the intensity of these peaks was observed, indicating that 60 min is the optimum time for the reaction via the sonication process. The appearance of the broad absorption peaks between 3,483 and 3,561 cm −1 indicates the moisture moiety (Figure a; Ofudje, Adeogun, Idowu, & Kareem, ; Ofudje et al, ). The existence of the absorption peaks in FTIR spectra at 1031, 949, 600, 563, and 516 cm −1 suggests the existence of phosphate moiety in the synthesized powder (Nasiri‐Tabrizi, Fahami, & Ebrahimi‐Kahrizsangi, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, after a certain time interval (60 min) no further enhancement in the intensity of these peaks was observed, indicating that 60 min is the optimum time for the reaction via the sonication process. The appearance of the broad absorption peaks between 3,483 and 3,561 cm −1 indicates the moisture moiety (Figure a; Ofudje, Adeogun, Idowu, & Kareem, ; Ofudje et al, ). The existence of the absorption peaks in FTIR spectra at 1031, 949, 600, 563, and 516 cm −1 suggests the existence of phosphate moiety in the synthesized powder (Nasiri‐Tabrizi, Fahami, & Ebrahimi‐Kahrizsangi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in their study, van Hengel et al [4] have shown that surfaces functionalized with zinc and silver ions exhibit antimicrobial activity, even against bacterial strains of methicillin-resistant Staphylococcus aureus (MRSA). The use of metallic ions (Silver and Zinc) as antimicrobial agents give to hydroxyapatite the ability to fight against gram-positive (Staphylococcus aureus, Streptococcus mutans, Bacillus cereus) [1,7,17,18], gram-negative (Escherichia coli, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum) [7,10] bacterial strains and fungi (Candida albicans) [1].…”
Section: Of 15mentioning
confidence: 99%
“…Due to Zn beneficial effects on bone formation, the synthesis of substituted HAP with Zn (HAP-Zn) has been carried out by using chemical precipitation methods for different Zn substitution levels into the HAP lattice. 16,[47][48][49][50] Silicon, Si, was found to be essential in bone growth and development. 51 This discovery has inspired the development of bioceramics based on Si-substituted hydroxyapatite (HAP-Si), [52][53][54][55][56][57] primarily by using precipitation routes.…”
Section: Introductionmentioning
confidence: 99%